# Evaluating SimPL in the Substitution Model

Let's begin by defining a small-step substitution-model semantics for SimPL. That is, we're going to define a relation --> that represents how an expression take a single step at a time, and we'll implement variables using substitution of values for names.

Recall the syntax of SimPL:

e ::= x | i | b | e1 bop e2
| if e1 then e2 else e3
| let x = e1 in e2

bop ::= + | * | <=


We're going to need to know when expressions are done evaluating, that is, when they are considered to be values. For SimPL, we'll define the values as follows:

v ::= i | b


That is, a value is either an integer constant or a Boolean constant.

## Defining the Single-Step Relation

For each of the syntactic forms that a SimPL expression could have, we'll now define some evaluation rules, which constitute an inductive definition of the --> relation. Each rule will have the form e --> e', meaning that e takes a single step to e'.

Although variables are given first in the BNF, let's pass over them for now, and come back to them after all the other forms.

Constants. Integer and Boolean constants are already values, so they cannot take a step. That might at first seem surprising, but remember that we are intending to also define a -->* relation that will permit zero or more steps; whereas, the --> relation represents exactly one step.

Technically, all we have to do to accomplish this is to just not write any rules of the form i --> e or b --> e for some e. So we're already done, actually: we haven't defined any rules yet.

Let's introduce another notation written e -/->, which is meant to look like an arrow with a slash through it, to mean "there does not exist an e' such that e --> e'. Using that we could write:

• i -/->
• b -/->

Though not strictly speaking part of the definition of -->, those propositions help us remember that constants do not step. In fact, we could more generally write, "for all v, it holds that v -/->."

Binary operators. A binary operator application e1 bop e2 has two subexpressions, e1 and e2. That leads to some choices about how to evaluate the expression:

• We could first evaluate the left-hand side e1, then the right-hand side e2, then apply the operator.

• Or we could do the right-hand side first, then the left-hand side.

• Or we could interleave the evaluation, first doing a step of e1, then of e2, then e1, then e2, etc.

• Or maybe the operator is a short-circuit operator, in which case one of the subexpressions might never be evaluated.

And there are many other strategies you might be able to invent.

It turns out that the OCaml language definition says that (for non-short-circuit operators) it is unspecified which side is evaluated first. The current implementation happens to evaluate the right-hand side first, but that's not something any programmer should rely upon.

Many people would expect left-to-right evaluation, so let's define the --> relation for that. We start by saying that the left-hand side can take a step:

e1 bop e2 --> e1' bop e2
if e1 --> e1'


Similarly to the type system for SimPL, this rule says that two expressions are in the --> relation if two other (simpler) subexpressions are also in the --> relation. That's what makes it an inductive definition.

If the left-hand side is finished evaluating, then the right-hand side may begin stepping:

v1 bop e2 --> v1 bop e2'
if e2 --> e2'


Finally, when both sides have reached a value, the binary operator may be applied:

v1 bop v2 --> v
if v is the result of primitive operation v1 bop v2


By primitive operation, we mean that there is some underlying notion of what bop actually means. For example, the character + is just a piece of syntax, but we are conditioned to understand its meaning as an arithmetic addition operation. The primitive operation typically is something implemented by hardware (e.g., an ADD opcode), or by a run-time library (e.g., a pow function).

For SimPL, let's delegate all primitive operations to OCaml. That is, the SimPL + operator will be the same as the OCaml + operator, as will * and <=.

Here's an example of using the binary operator rule:

    (3*1000) + ((1*100) + ((1*10) + 0))
--> 3000 + ((1*100) + ((1*10) + 0))
--> 3000 + (100 + ((1*10) + 0))
--> 3000 + (100 + (10 + 0))
--> 3000 + (100 + 10)
--> 3000 + 110
--> 3110


If expressions. As with binary operators, there are many choices of how to evaluate the subexpressions of an if expression. Nonetheless, most programmers would expect the guard to be evaluated first, then only one of the branches to be evaluated, because that's how most languages work. So let's write evaluation rules for that semantics.

First, the guard is evaluated to a value:

if e1 then e2 else e3 --> if e1' then e2 else e3
if e1 --> e1'


Then, based on the guard, the if expression is simplified to just one of the branches:

if true then e2 else e3 --> e2

if false then e2 else e3 --> e3


Let expressions. Let's make SimPL let expressions evaluate in the same way as OCaml let expressions: first the binding expression, then the body.

The rule that steps the binding expression is:

let x = e1 in e2 --> let x = e1' in e2
if e1 --> e1'


Next, if the binding expression has reached a value, we want to substitute that value for the name of the variable in the body expression:

let x = v1 in e2 --> e2 with v1 substituted for x


For example, let x = 42 in x+1 should step to 42+1, because substituting 42 for x in x+1 yields 42+1.

Of course, the right hand side of that rule isn't really an expression. It's just giving an intuition for the expression that we really want. We need to formally define what "substitute" means. It turns out to be rather tricky. So, rather then getting side-tracked by it right now, let's assume a new notation: e'{e/x}, which means, "the expression e' with e substituted for x." We'll come back to that notation in the next section and give it a careful definition.

For now, we can add this rule:

let x = v1 in e2 --> e2{v1/x}


Variables. Note how the let expression rule eliminates a variable from showing up in the body expression: the variable's name is replaced by the value that variable should have. So, we should never reach the point of attempting to step a variable name—assuming that the program was well typed.

Consider OCaml: if we try to evaluate an expression with an unbound variable, what happens? Let's check utop:

# x;;
Error: Unbound value x

# let y = x in y;;
Error: Unbound value x


It's an error (a type-checking error) for an expression to contain an unbound variable. Thus, any well-typed expression e will never reach the point of attempting to step a variable name.

As with constants, we therefore don't need to add any rules for variables. But, for clarity, we could state that x -/->.

## Implementing the Single-Step Relation

It's easy to turn the above definitions of --> into an OCaml function that pattern matches against AST nodes. In the code below, recall that we have yet finished defining substitution (i.e., subst); we'll return to that in the next section.

(** [is_value e] is whether [e] is a value. *)
let is_value : expr -> bool = function
| Int _ | Bool _ -> true
| Var _ | Let _ | Binop _ | If _ -> false

(** [subst e v x] is [e{v/x}]. *)
let subst e v x =
failwith "See next section"

(** [step] is the [-->] relation, that is, a single step of
evaluation. *)
let rec step : expr -> expr = function
| Int _ | Bool _ -> failwith "Does not step"
| Var _ -> failwith "Unbound variable"
| Binop (bop, e1, e2) when is_value e1 && is_value e2 ->
step_bop bop e1 e2
| Binop (bop, e1, e2) when is_value e1 ->
Binop (bop, e1, step e2)
| Binop (bop, e1, e2) -> Binop (bop, step e1, e2)
| Let (x, e1, e2) when is_value e1 -> subst e2 e1 x
| Let (x, e1, e2) -> Let (x, step e1, e2)
| If (Bool true, e2, _) -> e2
| If (Bool false, _, e3) -> e3
| If (Int _, _, _) -> failwith "Guard of if must have type bool"
| If (e1, e2, e3) -> If (step e1, e2, e3)

(** [step_bop bop v1 v2] implements the primitive operation
[v1 bop v2].  Requires: [v1] and [v2] are both values. *)
and step_bop bop e1 e2 = match bop, e1, e2 with
| Add, Int a, Int b -> Int (a + b)
| Mult, Int a, Int b -> Int (a * b)
| Leq, Int a, Int b -> Bool (a <= b)
| _ -> failwith "Operator and operand type mismatch"


The only new thing we had to deal with in that implementation was the two places where a run-time type error is discovered, namely, in the evaluation of If (Int _, _, _) and in the very last line, in which we discover that a binary operator is being applied to arguments of the wrong type. Type checking will guarantee that an exception never gets raised here, but OCaml's exhaustiveness analysis of pattern matching forces us to write a branch nonetheless. Moreover, if it ever turned out that we had a bug in our type checker that caused ill-typed binary operator applications to be evaluated, this exception would help us discover what was going wrong.

## The Multistep Relation

Now that we've defined -->, there's really nothing left to do to define -->*. It's just the reflexive transitive closure of -->. In other words, it can be defined with just these two rules:

e -->* e

e -->* e''
if e --> e' and e' -->* e''


Of course, in implementing an interpreter, what we really want is to take multiple steps until the expression reaches a value. That is, we want to take as many steps as possible. So, we're interested in the sub-relation e -->* v in which the right-hand side is a value. That's easy to implement:

(** [eval_small e] is the [e -->* v] relation.  That is,
keep applying [step] until a value is produced.  *)
let rec eval_small (e : expr) : expr =
if is_value e then e
else e |> step |> eval_small


## Defining the Big-Step Relation

Recall that our goal in defining the big-step relation ==> is to make sure it agrees with the multistep relation -->*.

Constants are easy, because they big-step to themselves:

i ==> i

b ==> b


Binary operators just big-step both of their subexpressions, then apply whatever the primitive operator is:

e1 bop e2 ==> v
if e1 ==> v1
and e2 ==> v2
and v is the result of primitive operation v1 bop v2


If expressions big step the guard, then big step one of the branches:

if e1 then e2 else e3 ==> v2
if e1 ==> true
and e2 ==> v2

if e1 then e2 else e3 ==> v3
if e1 ==> false
and e3 ==> v3


Let expressions big step the binding expression, do a substitution, and big step the result of the substitution:

let x = e1 in e2 ==> v2
if e1 ==> v1
and e2{v1/x} ==> v2


Finally, variables do not big step, for the same reason as with the small step semantics—a well-typed program will never reach the point of attempting to evaluate a variable name:

x =/=>


## Implementing the Big-Step Relation

The big-step evaluation relation is, if anything, even easier to implement than the small-step relation. It just recurses over the tree, evaluating subexpressions as required by the definition of ==>:

(** [eval_big e] is the [e ==> v] relation. *)
let rec eval_big (e : expr) : expr = match e with
| Int _ | Bool _ -> e
| Var _ -> failwith "Unbound variable"
| Binop (bop, e1, e2) -> eval_bop bop e1 e2
| Let (x, e1, e2) -> subst e2 (eval_big e1) x |> eval_big
| If (e1, e2, e3) -> eval_if e1 e2 e3

(** [eval_bop bop e1 e2] is the [e] such that [e1 bop e2 ==> e]. *)
and eval_bop bop e1 e2 = match bop, eval_big e1, eval_big e2 with
| Add, Int a, Int b -> Int (a + b)
| Mult, Int a, Int b -> Int (a * b)
| Leq, Int a, Int b -> Bool (a <= b)
| _ -> failwith "Operator and operand type mismatch"

(** [eval_if e1 e2 e3] is the [e] such that [if e1 then e2 else e3 ==> e]. *)
and eval_if e1 e2 e3 = match eval_big e1 with
| Bool true -> eval_big e2
| Bool false -> eval_big e3
| _ -> failwith "Guard of if must have type bool"


It's good engineering practice to factor out functions for each of the pieces of syntax, as we did above, unless the implementation can fit on just a single line in the main pattern match inside eval_big.